2022
DOI: 10.3389/fphys.2022.851957
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Transcriptome Sequencing Reveals Tissue-Specific Gene Expression Profile of Mangrove Clam Geloina erosa

Abstract: Mollusca is the second largest animal phylum and represents one of the most evolutionarily successful animal groups. Geloina erosa, a species of Corbiculidae, plays an important role in mangrove ecology. It is highly adaptable and can withstand environmental pollution and microbial infections. However, there is no reference genome or full-length transcriptome available for G. erosa. This impedes the study of the biological functions of its different tissues because transcriptome research requires reference gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The length of N50 was 1,617 bp, which was longer than that was found by Wang et al (2020) . High-quality transcripts were annotated using seven public databases, and the annotated transcript accounted for 88% of all transcripts, a similar rate to transcriptomics studies of Pinctada fucata martensii ( Zhang et al, 2020 ) and Mangrove Clam Geloina erosa ( Liao et al, 2022 ), but higher than reported by Wang et al (2020) . This indicates that the higher read lengths of SMRT sequencing compared to transcriptome sequencing increases annotated transcript percentages ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 63%
“…The length of N50 was 1,617 bp, which was longer than that was found by Wang et al (2020) . High-quality transcripts were annotated using seven public databases, and the annotated transcript accounted for 88% of all transcripts, a similar rate to transcriptomics studies of Pinctada fucata martensii ( Zhang et al, 2020 ) and Mangrove Clam Geloina erosa ( Liao et al, 2022 ), but higher than reported by Wang et al (2020) . This indicates that the higher read lengths of SMRT sequencing compared to transcriptome sequencing increases annotated transcript percentages ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 63%
“…This study combined the PacBio Iso-Seq and Illumina RNA-Seq technologies to generate a full-length transcriptome for M. lateralis. After correction, the average length of full-length consensus transcripts was 3,267 bp with an N50 of 3,879 bp (Table S2), which were much longer than that of the de novo assembled transcripts (Hu et al, 2019;Nie et al, 2021;Núñez-Acuña et al, 2022) and comparative with the full-length transcriptome of bivalve species recently reported (Liao et al, 2022;Zeng et al, 2022). The average mapping rate of Illumina sequences was greater than 75%, indicating that a good reference dataset was established.…”
Section: Resultsmentioning
confidence: 81%
“…With the continuous development of nucleic acid sequencing technology, the Pacific BioSciences (PacBio) single-molecule real-time (SMRT) sequencing, as the third-generation sequencing technology, has been utilized to generate full-length transcripts without assembly. Furthermore, the combined analysis of second-and third-generation sequencing could overcome the shortages of both technologies and is widely used currently (Grabherr et al, 2011;Cao et al, 2020;Luo et al, 2020;Liao et al, 2022). In bivalves, Zeng et al (2022) published the first report of full-length transcriptome regarding bivalve gonads in freshwater pearl mussels (Hyriopsis schlegelii), and Liao et al (2022) used a full-length transcriptome to reveal the tissue-specific gene expression profile of mangrove clam (Geloina erosa).…”
Section: Introductionmentioning
confidence: 99%
“…Another function involved in the high expression of miRNA in muscles is photoreceptive processes. In a previous study [56], it was found that genes associated with photoreception were highly expressed in muscle tissue. In this study, the gene F01.PB22530, regulated by miRNA gga-miR-133c-3p, exhibited retinal dehydrogenase activity.…”
Section: Muscle-specific Mirna and Target Gene Functionsmentioning
confidence: 92%